Study on cost and economy of Mountain micro-piles - Gan, Jingshuang; Xiao, Han (Transactions on Economics, Business and Management Research, 2024)
The State Grid Corporation of China has formulated relevant measures for further strengthening the management of mechanized construction, in order to promote the high-quality construction of the power grid and raise the level of mechanized construction of the power grid construction, improve the safety quality and efficiency of construction projects. At present, the construction of pole-tower foundation in mountain area mainly depends on manpower. It is very important to improve the level of power grid construction mechanization. This paper briefly introduces the characteristics and advantages of the mountain micro-pile foundation, discusses the cost items of the micro-pile in detail, and studies the economy of the mountain micro-pile by comparing the cost of the micro-pile with that of the common single pile